CORRELATION STUDIES IN HALF SIB FAMILIES OF THIRD CYCLE OF RECURRENT SELECTION IN SAFFLOWER (Carthamus tinctorius L.) - V.L. GAWANDE (The Journal of Research ANGRAU, 2023)
The investigation was undertaken to study the association of various characters for half sib families to yield and yieldattributing traits with an aim to select genotypes for developing population in next generation. Sixty plants having sufficient seedswere selected for evaluation and sown in augmented block design with AKS 207, Bhima, PBNS-12, A-1 and PKV Pink as checks.Observations were recorded on days to 50 % flowering, days to maturity on plot basis and plant height (cm), number of primarybranches plant-1, number of capitula plant-1, number of seeds per capitulum, 100 seed weight (g), seed yield plant-1 (g) and oilcontent (%) on plant basis. The correlation between days to 50% flowering and seed yield plant-1 was negative and significantindicating breaking of linkages. It also indicated that unfavourable gene combination can be broken by recurrent selectionmethods. In the study, in the safflower random mating population, seed yield plant-1 was significantly correlated with plant height(0.422**), no. of primary branches plant-1 (0.585**), number of capitula plant-1 (0.523**) and number of seeds per capitulum(0.27*). This indicated the importance of these traits while developing population for next generation.